2014
DOI: 10.1111/hex.12188
|View full text |Cite
|
Sign up to set email alerts
|

‘I'm happy that I can still walk’ – Participation of the elderly in home care as a specific group with specific needs and wishes

Abstract: Background Taking the needs, wishes and experiential knowledge of clients into account is considered to result in a better fit between the supply and demand of modern health care, contributing to the improvement of individual care, organizations, institutions and policy. However, the current generation of the elderly have had little experience of consumer-oriented public services. They are said to be less likely to discuss their needs and wishes with individual caregivers and health-care organisations. As a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Professionals do not often consider patients and informal caregivers to be part of the team . However, viewing patients and informal caregivers as team members is important for delivering high‐quality care, as some patients and informal caregivers have vital experiential knowledge and can therefore play crucial roles in the care‐provision process . Recognizing the roles of both patients and their informal caregivers in the team could help professionals to understand and collaborate better with them and thus limit the likelihood of challenges occurring in their interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Professionals do not often consider patients and informal caregivers to be part of the team . However, viewing patients and informal caregivers as team members is important for delivering high‐quality care, as some patients and informal caregivers have vital experiential knowledge and can therefore play crucial roles in the care‐provision process . Recognizing the roles of both patients and their informal caregivers in the team could help professionals to understand and collaborate better with them and thus limit the likelihood of challenges occurring in their interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The patient can be seen as the single binding factor of the primary care team, as actual care delivery should depend on a patient's specific wishes and needs . Various patient involvement models see the patient as an expert with experiential knowledge of their own condition that could complement the knowledge of professionals . Both patients and professionals often rely heavily on informal care .…”
Section: Introductionmentioning
confidence: 99%
“…Given the advantages of including patients’ perspectives, patients are increasingly involved in healthcare services (Bagchus et al 2014 ; Larsson et al 2007 ), healthcare quality (e.g. guideline development) (Pittens et al 2013 ) and health-related research (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…People have different ideas and preferences regarding participation [ 21 , 36 ]. Groot and Abma [ 37 ] found that different generations of older people have different preferences and needs in the participation process, linked to that particular generation.…”
Section: What Do Older People Expect From Participation?mentioning
confidence: 99%